2016
DOI: 10.1007/s12035-016-0136-4
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin-Loaded PEG-Gold Nanoparticles Enhanced the Neuroprotection of Anthocyanins in an Aβ1–42 Mouse Model of Alzheimer’s Disease

Abstract: Nanomedicine is an emerging research area. In this study, we investigated the neuroprotective efficacy of anthocyanin-loaded polyethylene glycol-gold nanoparticles (PEG-AuNPs) for enhancing the neuroprotective efficacy of anthocyanins in an amyloid beta (Aβ) mouse model of Alzheimer's disease. We observed that both anthocyanin-loaded PEG-AuNPs and anthocyanins treatment (12 μg/g/day for 14 days) ameliorated memory impairments in the Aβ-injected mice. However, the anthocyanin-loaded PEG-AuNPs were more effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 73 publications
4
59
0
Order By: Relevance
“…This enhancement is confirmed by Western blot analysis of the memory-associated presynaptic and postsynaptic protein markers [ 239 , 240 ] and by behavioral tests. Anthocyanins improve learning and memory, which has been confirmed by the Morris water maze [ 240 , 243 , 244 , 245 , 252 , 253 , 254 , 260 , 264 , 265 , 266 ], Y-maze [ 240 , 255 ], novel object recognition [ 241 , 248 , 260 , 265 ] and passive avoidance [ 245 , 254 , 263 ] tests. Motor coordination is also improved by anthocyanins as confirmed by rotating rod test [ 244 ] and open-field [ 248 , 263 ] tests.…”
Section: Anthocyanins’ Health Effects On Cardiovascular and Neurodmentioning
confidence: 74%
See 1 more Smart Citation
“…This enhancement is confirmed by Western blot analysis of the memory-associated presynaptic and postsynaptic protein markers [ 239 , 240 ] and by behavioral tests. Anthocyanins improve learning and memory, which has been confirmed by the Morris water maze [ 240 , 243 , 244 , 245 , 252 , 253 , 254 , 260 , 264 , 265 , 266 ], Y-maze [ 240 , 255 ], novel object recognition [ 241 , 248 , 260 , 265 ] and passive avoidance [ 245 , 254 , 263 ] tests. Motor coordination is also improved by anthocyanins as confirmed by rotating rod test [ 244 ] and open-field [ 248 , 263 ] tests.…”
Section: Anthocyanins’ Health Effects On Cardiovascular and Neurodmentioning
confidence: 74%
“…Additionally, anthocyanin-loaded polyethylene glycol-gold nanoparticles (PEG-AuNPs) regulate the p-PI3K/p-Akt/p-GSK3β pathway in the amyloid beta (Aβ)1–42 mouse model of Alzheimer’s disease. This regulation prevented the appearance of the tau protein during the hyperphosphorylation of serines 413 and 404 [ 240 ]. Blueberry attenuates radiation-induced oxidative stress in rats through attenuation of nicotinamide adenine dinucleotide phosphate as well as activation of Nrf2 [ 241 ].…”
Section: Anthocyanins’ Health Effects On Cardiovascular and Neurodmentioning
confidence: 99%
“…Further, anthocyanin-rich supplements can inhibit tau hyperphosphorylation in the hippocampus and improve performance on cognitive behavioral tests as shown in mouse models of AD. 56 Our recent published studies 30,32 demonstrated that 12-week consumption of tart cherry juice lowered systolic BP by 4 mmHg and CRP by 25% as well as increased the plasma levels of DNA repair activity of OGG1. This supports the notion that the improvements in cognitive performance by tart cherry juice consumption may be due to its anti-inflammatory and anti-oxidative properties, and through a lowering of BP.…”
Section: Figmentioning
confidence: 98%
“…These observations indicate the ability of quercetin to decrease tau protein hyperphosphorylation and thereby to attenuate the associated neuropathology ( Figure 4) [79]. Anthocyanins were reported to activate the phosphorylation of anti-phosphorylated GSK3β at Ser 9, thereby possibly preventing GSK-3β-dependent tau hyperphosphorylation at Ser 413 and 404 [80]. GSPA is also able to decrease hyperphosphorylated tau deposition in APP/PS1 male heterozygous mice (Figure 4) [76].…”
Section: Targeting Tau Proteinmentioning
confidence: 90%